The Use of Macromedia Flash Animation to Enhance Studentsâ English Writing Skill at the Seventh Grade of SMP Yapis 1 Fakfak-West Papua - Lisda, Wa; Rahman, Muhammad Asfah; Atmowardoyo, Haryanto (Program Pascasarjana Universitas Negeri Makassar, 2015)
This research is conducted to find out: (1) whether the use of macromedia flash animation enhance studentsâ writing skill or not; (2) the studentsâ interest in English writing class using macromedia flash animation; (3) whether studentâs interest have relationship to studentâs writing ability or not.The research employs quasi-experimental method. The sample consists of 51 students which belongs to two groups; 27 students in experimental group and 24 students in control group. The data are collected by writing test (pre-test and post-test) and questionnaire which is analyzed through SPSS 20.0. In conducting the research, the researcher applies macromedia flash animation as the medium to experimental group while the teacher in the control group uses power point presentation. The research results indicated that macromedia flash animation can enhance studentsâ English writing skill at the seventh grade students of SMP Yapis 1 Fakfak-West Papua in academic year 2014/2015. Although the mean score of experimental group is higher than the mean score of control group, it does not show asignificant difference (73.93>70.33). Therefore, based on pair test, the result shows that the mean score of pre-test and post-test in experimental group are significantly different (55.41-73.93). Moreover, based on the studentsâ response on the questionnaire, it is found that the mean score is 80.15 which was categorized âinterestedâ. The Pearsonâs r for correlation shows that the correlation coefficient between studentsâ interest and studentsâ writing ability is 0.891, with the sig. (2 tailed) value is less than 0.05 indicates that there is a strong, significant and positive correlation between studentsâ interest and studentsâ writing ability. Specifically, the research result indicates that macromedia flash animation is interesting and effective to enhance studentsâ writing skill. Key words: macromedia flash animation, writing skill, interest.